(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Ducks, geese, and swans are members of the Anatidae biological family of aquatic birds. Thefamily has a global distribution, with the exception of Antarctica, occurring on all of the world’scontinents. These birds have evolved to be able to swim and float on the water’s surface. There arearound 174 species in 43 genera in the family. (The magpie goose is now classified as its own family,Anseranatidae, and no longer belongs to the Anatidae.)They are herbivorous and monogamous breeders in general. Annual migrations are carried out by avariety of species. Many animals have been tamed for agricultural purposes, while others are hunted forfood and enjoyment. Since 1600, five species have gone extinct, and many more are on the verge ofextinction. This paper deals with the brief study on important aspects of waterfowls belong to FamilyAnatidae.